BIPARIETAL DIAMETER FIXED INCOME FOR THE CALCULATION OF FETAL ULTRASOUND DETERMINED BY WEIGHT - Fiestas, Carlos (2015)
OBJECTIVE: To determine the usefulness of the corrected biparietal diameter to calculate fetal weight by ultrasound. DESING: Prospective study. SETTING: Cayetano Heredia Hospital, Piura, Peru. PATIENTS: Term pregnant women. Interventions: From January through May 2006, biparietal diameter (BPD), occipitofrontal  diameter (OFD), corrected biparietal diameter (cBPD), femur length (FL), and abdominal perimeter (AP) were determined. Fetal weight was calculated by Hadlock’s parameters, by biparietal diameter in the first group and corrected biparietal diameter in the second group and both were correlated with the newborn weight (NBW). Interval between ultrasound examination and delivery was less than 72 hours. MAIN OUTCOME MEASURES: Correlation of both biparietal diameter and corrected biparietal diameter with newborn weight. RESULTS: Average mother’s age was 26,8 ± 6,4 years. Average newborn weight was 3215 g. BPD estimated fetal weight averaged 3212 g, percentage error was 5,55%, standard error 130 g and correlation 0,888. For cBPD, estimated fetal weight averaged 3320 g, percentage error 5,85%, standard error 127 g and correlation 0,858.  CONCLUSION: Hadlock’s corrected biparietal diameter instead of regular biparietal diameter did not appear useful to calculate fetal weight by ultrasound.